BDNF-TrkB Signaling Coupled to nPKCε and cPKCβI Modulate the Phosphorylation of the Exocytotic Protein Munc18-1 During Synaptic Activity at the Neuromuscular Junction - Simó, Anna; Just-Borràs, Laia; Cilleros-Mañé, Víctor; Hurtado, Erica; Nadal, Laura; Tomàs, Marta; Garcia, Neus; Lanuza, Maria A.; Tomàs, Josep (Frontiers in Molecular Neuroscience, 2018)
Munc18-1, a neuron-specific member of the Sec1/Munc18 family, is involved in neurotransmitter release by binding tightly to syntaxin. Munc18-1 is phosphorylated by PKC on Ser-306 and Ser-313 in vitro which reduces the amount of Munc18-1 able to bind syntaxin. We have previously identified that PKC is involved in neurotransmitter release when continuous electrical stimulation imposes a moderate activity on the NMJ and that muscle contraction through TrkB has an important impact on presynaptic PKC isoforms levels, specifically cPKCβI and nPKCε. Therefore, the present study was designed to understand how Munc18-1 phosphorylation is affected by (1) synaptic activity at the neuromuscular junction, (2) nPKCε and cPKCβI isoforms activity, (3) muscle contraction per se, and (4) the BDNF/TrkB signaling in a neuromuscular activity-dependent manner. We performed immunohistochemistry and confocal techniques to evidence the presynaptic location of Munc18-1 in the rat diaphragm muscle. To study synaptic activity, we stimulated the phrenic nerve (1 Hz, 30 min) with or without contraction (abolished by μ-conotoxin GIIIB). Specific inhibitory reagents were used to block nPKCε and cPKCβI activity and to modulate the tropomyosin receptor kinase B (TrkB). Main results obtained from Western blot experiments showed that phosphorylation of Munc18-1 at Ser-313 increases in response to a signaling mechanism initiated by synaptic activity and directly mediated by nPKCε. Otherwise, cPKCβI and TrkB activities work together to prevent this synaptic activity–induced Munc18-1 phosphorylation by a negative regulation of cPKCβI over nPKCε. Therefore, a balance between the activities of these PKC isoforms could be a relevant cue in the regulation of the exocytotic apparatus. The results also demonstrate that muscle contraction prevents the synaptic activity–induced Munc18-1 phosphorylation through a mechanism that opposes the TrkB/cPKCβI/nPKCε signaling.